Bayesian simultaneous determination of structural breaks and lag lengths - Brigitta Hultblad (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
The detection of structural change and determination of lag lengths are long-standing issues in time series analysis. This paper demonstrates how these can be successfully married in a Bayesian analysis. By taking account of the inherent uncertainty about the lag length when deciding on the number of structural breaks and vice versa we avoid some common pitfalls and are able to draw more robust conclusions. The approach is illustrated using both real and simulated data.
Keywords: C11; C15; C22; C51; 330; Regime shifts; Model uncertainty; Model averaging; Markov chain Monte Carlo; Real interest rate; Zeitreihenanalyse; Lag-Modell; Realzins; Markovscher Prozess; Entscheidung bei Unsicherheit